ANALISIS DESAIN DAN TATA KELOLA IMPLEMENTASI KURIKULUM SALAF DENGAN PAKET KESETARAAN PENDIDIKAN FORMAL DI PONDOk PESANTREN ZAINUL HASANAIN - Syadidil Ithqon; Ismatul Izzah; Arifia Retna Yunita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the design of the salaf curriculum in Madrasah Diniyah Mu’allimin, the alignment between the salaf curriculum and the standards of the Equality Education Package Program, and the governance of dual-curriculum implementation at Pondok Pesantren Zainul Hasanain. This research employs a descriptive qualitative approach, with the researcher as the main instrument. Data are planned to be collected through interviews, observation, and documentation, then analyzed using an interactive thematic analysis. This study is grounded in the need to integrate formal and non-formal education, which requires alignment of objectives, content, methods, assessment, and managerial accountability. Recent studies show that the success of curriculum integration in Islamic boarding schools is strongly influenced by curriculum management, harmonization with the national curriculum, adaptive governance, and structured management of equality education programs through the functions of planning, organizing, implementing, and evaluating. This study is expected to produce a mapping of curriculum design, identify supporting and inhibiting factors, and formulate operational recommendations so that the integration of the salaf curriculum and the equality education package can run effectively without eliminating the distinctive character of the pesantren.